2014
DOI: 10.1371/journal.pone.0090574
|View full text |Cite|
|
Sign up to set email alerts
|

A Unique Mutation in a MYB Gene Cosegregates with the Nectarine Phenotype in Peach

Abstract: Nectarines play a key role in peach industry; the fuzzless skin has implications for consumer acceptance. The peach/nectarine (G/g) trait was described as monogenic and previously mapped on chromosome 5. Here, the position of the G locus was delimited within a 1.1 cM interval (635 kb) based on linkage analysis of an F2 progeny from the cross ‘Contender’ (C, peach) x ‘Ambra’ (A, nectarine). Careful inspection of the genes annotated in the corresponding genomic sequence (Peach v1.0), coupled with variant discove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 80 publications
(108 reference statements)
4
85
1
2
Order By: Relevance
“…The fruit glabrous trait (nectarine) was recently associated with a recessive transposable element insertion in an MYB gene ( ppa026143m ) on scaffold_5, located in the 15,897,836 to 15,899,002 bp interval5. The present results revealed that the SNP that was mostly associated to fruit hairiness was located in the 17,576,893 bp of scaffold_5, with a −log 10 P value of 121.92 and a minor allele frequency of 0.22, corresponding to 1.7 Mb distance of ppa026143m (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fruit glabrous trait (nectarine) was recently associated with a recessive transposable element insertion in an MYB gene ( ppa026143m ) on scaffold_5, located in the 15,897,836 to 15,899,002 bp interval5. The present results revealed that the SNP that was mostly associated to fruit hairiness was located in the 17,576,893 bp of scaffold_5, with a −log 10 P value of 121.92 and a minor allele frequency of 0.22, corresponding to 1.7 Mb distance of ppa026143m (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, this may have only been possible in peach due to its low rate of polymorphism, resulting from self-pollination and grafting7. On the other hand, results for fruit hairiness and fruit flesh colour were not consistent with the results of gene identification obtained through reverse genetics45. This inconsistency might be due to fruit hairiness and fruit flesh colour being determined by the insertion of transposable elements45, a type of variation difficult to screen using next-generation sequencing with low sequence depth, and that cannot be identified by GWAS, using SNPs only.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, SNPs occur in both coding and non-coding regions of genes and may influence gene function by determining changes in the encoded amino acid (non-synonymous SNPs). These functional changes could be responsible for phenotypic changes in plants (Martínez-Gómez et al 2012;Adami et al 2013;Vendramin et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Finally, SNP analysis via the Sequenom approach has been used in peach for the fine mapping of the genomic region controlling maturity date in scaffold 4 ) and of the G locus in scaffold 5 (Vendramin et al 2014). In both cases, this approach made it possible to identify a candidate gene responsible for these traits.…”
Section: Introductionmentioning
confidence: 99%